Structural perspectives on axon guidance - Seiradake, E; Jones, E; Klein, R (Annual Reviews, 2016)
Axon guidance relies on a combinatorial code of receptor and ligand interactions that direct adhesive/attractive and repulsive cellular responses. Recent structural data have revealed many of the molecular mechanisms that govern these interactions and enabled the design of sophisticated mutant tools to dissect their biological functions. Here, we discuss the structure/function relationships of four major classes of guidance cues (ephrins, semaphorins, slits, netrins) and examples of morphogens (Wnt, Shh) and of cell adhesion molecules (FLRT). These cell signaling systems rely on specific modes of receptor-ligand binding that are determined by selective binding sites; however, defined structure-encoded receptor promiscuity also enables cross talk between different receptor/ligand families and can also involve extracellular matrix components. A picture emerges in which a multitude of highly context-dependent structural assemblies determines the finely tuned cellular behavior required for nervous system development. Expected final online publication date for the Annual Review of Cell and Developmental Biology Volume 32 is October 06, 2016. Please see http://www.annualreviews.org/catalog/pubdates.aspx for revised estimates.